PREVALENCE, KNOWLEDGE AND SELF-EFFICACY OF BURNOUT SYNDROME AMONG PRIMARY HEALTHCARE WORKERS IN JOHOR BAHRU, MALAYSIA: PREVALENCE, KNOWLEDGE AND SELF-EFFICACY OF BURNOUT SYNDROME AMONG PRIMARY HEALTHCARE WORKERS IN JOHOR BAHRU, MALAYSIA - Rahmat Dapari; Ab Razak, Muhamad Farhan; Hamedon, Titi Rahmawati; Toha, Haidar Rizal (Malaysian Journal of Public Health Medicine, 2025)
Primary healthcare workers (PHCW) were prone to develop burnout syndrome because the needs of giving comprehensive care towards their clients. With increased number of clients under their care, in addition to administrative works, this will create a huge burden on them. Studies have shown that PHCW have high prevalence of burnout syndrome. This will give negative implication on their mental health, quality of healthcare services and social life. Despite the growing number of burnout syndrome among PHCW, there is no intervention done to reduce the burnout syndrome. The aim of the study is to determine the prevalence of burnout syndrome as well as knowledge on burnout syndrome, self-efficacy and its associated factors before commencing the Health Education Module (HMDS) intervention. A cross-sectional study with sample size of 198 healthcare workers from fourteen government health clinics in Johor Bahru was conducted. Simple random sampling on doctors, nurses and assistant medical officers from each clinic were utilized. Self-administered question was used to obtain information on sociodemographic, job characteristic, burnout score (Copenhagen Burnout Inventory), knowledge score and self-efficacy score (General Self-Efficacy Scale). Data was clean and analysed accordingly. Significant level was taken at p=0.05. Majority of respondent age between 30 to 39 years, female, Malay, married, have diploma, works as nurse, has working experience between 1 to 5 years and earn more than RM6000 per month. There were 46.1% of respondent has personal burnout, 34.6% has work-related burnout and 25.7% has client related burnout. Gender, ethnicity, education level, occupation, knowledge score and self-efficacy score shows significant association with burnout syndrome. Intervention on burnout syndrome among PHCW need to be done through health education on burnout syndrome and its coping strategies.